Iron therapy for iron-deficiency anemia and pelvic inflammatory disease - Khaiatova Z.B; Abdukadirova N.B; A.V. Yakimova; Shpagina L.A; Sokolova T.M (LCC «Medicine-Inform», 2019)
Iron therapy for iron-deficiency anemia and pelvic inflammatory disease Z.B. Khaiatova1, N.B. Abdukadirova2, A.V. Yakimova1, L.A. Shpagina1, T.M. Sokolova1 1Novosibirsk State Medical University, Novosibirsk, Russian Federation 2Samarkand State Medical Institute, Samarkand, Uzbekistan Aim: To assess the efficacy of two-step treatment for iron-deficiency anemia in women of reproductive age with pelvic inflammatory disease (PID). Patients and Methods: 320 women with iron-deficiency anemia and pelvic inflammatory disease were subdivided into two groups depending on the treatment. Group I included 160 women who received traditional therapy, i.e., complex treatment for pelvic inflammatory disease plus Tardyferon® for iron-deficiency anemia. Group II included 160 women who received stepwise treatment. Step 1 was complex treatment for pelvic inflammatory disease only. After the inflammation has reduced and iron-deficiency anemia was verified, the patients were prescribed (on average, after 12.2±1.1 days) with Tardyferon® (step 2). Results: Serum tests have demonstrated that these women are characterized by high activity of free radical processes which illustrate active inflammation. After 10 days of the treatment, the ratio of pro-oxidant and antioxidant activities was significantly less in group I than in group II. Moreover, in group I this ratio has significantly increased. In group I, the result of the treatment was increased pro-oxidant potential. Reduced serum antioxidant activity has resulted in the oxidative stress. After 30 days, average hemoglobin, serum iron, and serum ferritin in group II women with iron-deficiency anemia (both stage 1 and 2) were significantly higher than in group I women. Despite complex anti-inflammatory treatment for PID, vaginitis was diagnosed in 20.6% (n=33) in group I. Conclusions: Two-step treatment for iron-deficiency anemia in women with PID using Tardyferon® is highly effective which is illustrated by the normalization of ferrokinetic parameters, decrease in pro-oxidant activity, less common (by 3.1 times) inflammatory signs, and less common (by 2.1 times) iron deficiency signs. Keywords: iron-deficiency anemia, ferritin, pelvic inflammatory disease. For citation: Khaiatova Z.B., Abdukadirova N.B.,Yakimova A.V. et al. Iron therapy for iron-deficiency anemia and pelvic inflammatory disease. Russian Journal of Woman and Child Health. 2019;2(2):108-112.